Standardization of clinical pharmacist's activities: Methodology - Jana Gregorová; Jitka Rychlíčková; Jan Šaloun (Elsevier, 2017)
Study objectives: Establishing standardized and controlled system of work at a clinical pharmacy department and establishing effective recording of activities of a group of four clinical pharmacist when providing clinical pharmaceutical care (CPC) in a hospital. Methods: The duration of evaluated period is 5.5 years. The first part was defining the purpose, methods and activities of clinical pharmaceutical care, the next part was designing the software for recording patient's data and CPC activities. To verify the functionality of our system the third part was conducted (from January 1, 2015 to June 30, 2015). Results: CPC activities were defined precisely. During the 6 months period, 3946 patients were reviewed (17% of patients admitted), in this group, 41% patients was labeled as risk (these patients had one or more risk factor). 1722 repeated reviews were performed, 884 drug therapy recommendations were recorded. The calculated average time necessary for one CPC activity is 28 min. Conclusion: During the 5 year period, standardized system of work in clinical pharmacy department was established. This system is based on clearly defined activities and it enables external control. Our results supply data for negotiations with health insurance companies.